1986
DOI: 10.1136/thx.41.12.903
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid treatment in pulmonary sarcoidosis: do serial lavage lymphocyte counts, serum angiotensin converting enzyme measurements, and gallium-67 scans help management?

Abstract: Thirty two patients with persisting pulmonary sarcoidosis fulfilling defined criteria for treatment were managed according to a standard clinical protocol. In this an attempt was made to achieve and maintain maximal radiographic and physiological improvement with individually titrated doses of corticosteroids. Lavage cell counts, serum angiotensin converting enzyme (SACE) determinations, and gallium-67 scans were planned at standard intervals but were not used in management decisions. The study analysed serial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 10 publications
5
28
0
Order By: Relevance
“…Although lack of serial measurements (before and after therapy administration) limits definite conclusions this finding suggests a reduction of oxidative stress under the influence of systemic corticosteroids. This is in accordance to the already known immunomodulatory role of corticosteroids and their ability to suppress inflammation by activating anti-inflammatory genes or by disabling inflammatory genes [23]. The complex interactions between inflammation and redox-related pathways which have already been described might also explain the lower systemic oxidative stress in patients receiving corticosteroids.…”
Section: A C C E P T E D Article In Presssupporting
confidence: 87%
“…Although lack of serial measurements (before and after therapy administration) limits definite conclusions this finding suggests a reduction of oxidative stress under the influence of systemic corticosteroids. This is in accordance to the already known immunomodulatory role of corticosteroids and their ability to suppress inflammation by activating anti-inflammatory genes or by disabling inflammatory genes [23]. The complex interactions between inflammation and redox-related pathways which have already been described might also explain the lower systemic oxidative stress in patients receiving corticosteroids.…”
Section: A C C E P T E D Article In Presssupporting
confidence: 87%
“…Many studies have shown quite conclusively that steroids can improve chest radiographic features and lung function measurements, and these include some of those studies which conclude that there was no long-term benefit on disease outcome (but see below) [59][60][61][62][63][64]. ODLUM and FITZGERALD [62] studied six patients who had been untreated for a period of 6.8±2.4 yrs and whose disease was demonstrated to be progressing.…”
Section: Corticosteroids and Clinical Efficacymentioning
confidence: 99%
“…TURNER-WARWICK et al [64] treated 32 patients with a standard treatment which was then titrated to maintain maximum improvement. Results showed that chest radiographs improved in all 32 and were not related to the initial BAL lymphocytes count.…”
Section: Corticosteroids and Clinical Efficacymentioning
confidence: 99%
“…Since the cells recovered in bronchoalveolar lavage (BAL) fluid reflect the alveolitis [3], the analysis of BAL cell populations, especially lymphocyte count and T-cell subsets, has largely been used to define prognostic markers [4][5][6][7][8][9][10][11][12][13][14][15][16]. Some investigators reported that a high BAL lymphocyte count was associated with a higher risk of pulmonary function deterioration [4,9] and with a better response to steroid therapy [7], whilst others found that the helper to suppressor T-cell ratio (T4/T8) was more reliable [5,8].…”
Section: -Pi) Expressed As a Relative Coefficient Of Excretion (Rce)mentioning
confidence: 99%